How does reorganisation in child and adolescent mental health services affect access to services? An observational study of two services in England. - Mina Fazel; Stephen Rocks; Margaret Glogowska; Melissa Stepney; Apostolos Tsiachristas (PLoS ONE)
Background Child and Adolescent Mental Health Services (CAMHS) in England are making significant changes to improve access and effectiveness. This 'transformation' variously involves easier access to services through a Single Point of Access (SPA), more integrated services within CAMHS and enhanced co-provision across education and third sector or non-profit organisations. Methods A mixed-methods observational study was conducted to explore the process and impact of transformation over four years in two services. Ethnographic observations and in-depth interviews were conducted and Electronic Patient Records with over one million contacts analysed. Difference-in-differences analysis with propensity score matching to estimate the causal impact of the transformation on patient access was utilised. Outcomes Spend and staffing increased across both CAMHS. The SPA had growing rates of self-referral and new care pathways were seeing patients according to expected degree of psychopathology. Third sector partners were providing increasing numbers of low-intensity interventions. Although the majority of staff were supportive of the changes, the process of transformation led to service tensions. In the first year after transformation there was no change in the rate of new patients accessing services or new spells (episodes of care) in the services. However, by year three, the number of new patients accessing CAMHS was 19% higher (Incidence Rate Ratio: 1·19, CI: 1·16, 1·21) and the rate of new spells was 12% higher (Incidence Rate Ratio: 1·12, CI: 1·05, 1·20). Interpretation Transformation investment, both financial and intellectual, can help to increase access to CAMHS in England, but time is needed to realise the benefits of reorganisation.